Binding of tetracycline to its aptamer determined by 2D-correlated Mn2+ hyperfine spectroscopy - Hetzke, T; Bowen, A; Vogel, M; Gauger, M; Suess, B; Prisner, T (Elsevier, 2019)
The tetracycline-binding RNA aptamer (TC-aptamer) binds its cognate ligand the antibiotic tetracycline (TC) via a Mg2+ or Mn2+ ion with high affinity at high divalent metal ion concentrations (KD=800pM, ⩾10 mM). These concentrations lie above the physiological divalent metal ion concentration of ca. 1 mM and it is known from literature, that the binding affinity decreases upon decreasing the divalent metal ion concentration. This work uses a Mn2+ concentration of 1 mM and 1D-hyperfine experiments reveal two pronounced 31P couplings from the RNA besides the 13C signal of 13C-labeled TC. From these 1D-hyperfine data alone, however, no conclusions can be drawn on the binding of TC. Either TC may bind via Mn2+ to the aptamer or TC may form a free Mn-TC complex and some Mn2+ also binds to the aptamer. In this work, we show using 2D-correlated hyperfine spectroscopy at Q-band frequencies (34 GHz), that the 13C and 31P signals can be correlated; thus arising from a single species. We use THYCOS (triple hyperfine correlation spectroscopy) and 2D ELDOR-detected NMR (2D electron electron double resonance detected NMR) for this purpose showing that they are suitable techniques to correlate two different nuclear spin species (13C and 31P) on two different molecules (RNA and TC) to the same electron spin (Mn2+). Out of the two observed 31P-hyperfine couplings, only one shows a clear correlation to 13C. Although THYCOS and 2D EDNMR yield identical results, 2D EDNMR is far more sensitive. THYCOS spectra needed a time factor of ×20 in comparison to 2D EDNMR to achieve a comparable signal-to-noise.